Proceedings of the 1st International Conference on Science, Health, Economics, Education and Technology (ICoSHEET 2019) 2020
DOI: 10.2991/ahsr.k.200723.058
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Age, Working and Education With/Regarding the Quality of Live of Elderly

Abstract: An increase in life expectancy occurs with advances in science and technology. The increase in life expectancy raises one of the consequences, namely the increasing number of the elderly population. In general, elderly people face weaknesses, limitations, and disabilities, so that the quality of life of the elderly decreases. One of the influences on the quality of life of the elderly is age, the age of pre-elderly is the quality of life that will be better compared to those who have continued age. Besides, wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
2
1
Order By: Relevance
“…Findings from this study did not indicate a correlation between age and pandemic-related quality of life, contrary to literature which indicates an association between age and decline in quality of life, particularly among the elderly over the age of 75 [18]. This is attributed to the limitations and disabilities which develop with aging, lowering their quality of life [19]. Similarly, a study from the United Kingdom found that those over the age of 50 will experience a 4-year decline in their quality of life.…”
Section: Relationship Between Age Gender and Employment Status With Q...contrasting
confidence: 99%
See 1 more Smart Citation
“…Findings from this study did not indicate a correlation between age and pandemic-related quality of life, contrary to literature which indicates an association between age and decline in quality of life, particularly among the elderly over the age of 75 [18]. This is attributed to the limitations and disabilities which develop with aging, lowering their quality of life [19]. Similarly, a study from the United Kingdom found that those over the age of 50 will experience a 4-year decline in their quality of life.…”
Section: Relationship Between Age Gender and Employment Status With Q...contrasting
confidence: 99%
“…The coronavirus disease (COVID- 19) is an infectious disease caused by the SARS-CoV-2 virus. Most people infected with the virus will develop mildto-moderate respiratory symptoms and recover without requiring special treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple factors, including muscle mass, muscle strength, genetics, the existence of chronic diseases, level of physical activity, mental wellness, and psychosocial factors, influence the physical performance of older adults. 4 8 Muscle mass is vital to the physical performance of older adults. The age-related loss of muscle mass, also known as sarcopenia, is recognized as the primary element underlying the decline in physical performance among older adults.…”
Section: Introductionmentioning
confidence: 99%